P624 A higher prevalence of human papillomavirus in patients with perianal fistulizing Crohn's disease compared to patients with anorectal fistula without Crohn's disease. (27th May 2021) - Rodrigues Boarini, L; Sobrado Jr, C W; Facanali, C B G; Queiroz, N S F; Albuquerque, I C; Boarini, P; Boarini, M R; Borba, M R; Nahas, S C; Cecconello, I
Abstract: Background: Perianal fistulizing Crohn's disease (PFCD) is the main risk factor for anal cancer in patients with inflammatory bowel disease. It is not known whether this occurs due to a higher frequency of human papillomavirus (HPV) in this population or due to the chronic inflammatory condition resulting from perianal fistulas. We aimed to evaluate whether there is a higher prevalence of HPV and high-risk HPV in patients with PFCD compared to the control group, estimate the prevalence of HPV and the subtypes most frequently associated with PFCD. Methods: We performed a bicentric cross sectional study in which participants were matched by age and sex. A total of 108 patients with surgical indication for perianal fistula, were recruited, 54 patients in PFCD group and 54 patients with anorectal fistula without Crohn's disease, from December 2018 through November 2020. These patients were subject to histological material collection during exam under anesthesia with biopsy of the fistulous pathway. The sample was sent for HPV detection and genotyping by INNO-LiPA HPV Genotyping Extra II. Results: The PFCD group showed a statistically higher frequency of HPV in the fistulous path compared to control group (33.3% vs 16.7%, p = 0.046). The isolated analysis of the high-risk subtypes numerically demonstrated double the frequency in PFCD group, however, not statistically significant (18.5% vs 9.3%, p = 0.164). After multiple logistic regressions, patients with PFCD had a chance of HPV 3.42 times higher than patients without Crohn's disease (OR = 3.42, 95% CI, 1.25–9.40), regardless of other variables. The subtypes most frequently identified in PFCD group were HPV11 (12.72%) and HPV16 (9.09%). Conclusion: Perianal fistulizing Crohn's disease is associated with a higher prevalence of HPV compared to patients with anorectal fistula without Crohn's disease.